PERAN KOMIK DIGITAL SEBAGAI MEDIA PEMBELAJARAN BAHASA INDONESIA YANG INOVATIF DAN KREATIF - Ni Komang Sinta Paingningsih; Komang Trisna mahartini; Putu Yulia Angga Dewi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The development of digital technology in the modern era demands that the world of education provides learning media that are creative, innovative, and appropriate to the character of students. However, in practice, Indonesian language learning is still dominated by conventional methods that are less interesting, resulting in minimal learning motivation and low student understanding of the material. This problem indicates the need for learning media that can integrate visual elements, text, and interactivity, one of which is through the use of digital comics. This study aims to describe the role of digital comics as an innovative and creative Indonesian language learning medium and explain how the media contributes to increasing student motivation, engagement, and understanding. The method used in this study is a literature study, namely by analyzing various previous studies, national journals, scientific articles, and relevant books related to the use of digital comics in learning. The literature study procedure includes source collection, classification, thematic analysis, and synthesis of research results. The results of the study indicate that digital comics have a significant role as a learning medium that can increase the appeal of the material, facilitate understanding of text concepts, foster student creativity, and create a more interactive learning atmosphere. Digital comics have also been proven effective in developing students' visual literacy and reading literacy skills. In conclusion, digital comics are a suitable alternative for innovative and creative Indonesian language learning media, and can support improving the quality of teaching and learning in the digital era.